EFFECT OF ORGANIZATIONAL COMMITMENT, WORK MOTIVATION AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE OF PT. ACEH DISTRIBUS INDO RAYA - likdanawati, likdanawati; Yanita, Yanita; Hamdiah, Hamdiah; Nur Ilham, Rico; Sinta, Irada (RADJA PUBLIKA, 2022)
This study aims to determine the Effect of Organizational Commitment, Work Motivation and Leadership Style on employee performance of PT. Aceh Distribution Indo Raya. The study samples are 54 employees of PT. Aceh Distribution Indo Raya. The sampling technique used is a probability sampling technique. The data are obtained from the distribution of questionnaires to 54 respondents and processed with the help of the SPSS program. The method of data analysis used a qualitative analysis method that is quantified. The model used in this study is a multiple linear regression. The results of the study show that simultaneously (f-test) Organizational Commitment, Work Motivation and Leadership Style influence the Employee Performance of PT. Aceh Distribution Indo Raya. Based on the results partially (t-test) shows that Organizational Commitment has a significant effect on Employee Performance of PT. Aceh Distribus Indo Raya, Work Motivation has a significant effect on Employee Performance at PT. Aceh Distribus Indo Raya and Leadership Style has a significant effect on the Employee Performance of PT. Aceh Distribution Indo Raya.